Pediatric bone : biology and diseases - Glorieux, Francis H.; Pettifor, John M.; Juppner, Harald (Academic Press, 2003)
Pediatric Bone is the first book to be published to deal exclusively with the biology and diseases of bone as they affect children. Rapid advances have been made in our understanding of the mechanisms and factors controlling the growth and development of bone, and these are discussed in detail in this book. Further, the various diseases of bone which are peculiar to children are highlighted and discussed in the light of our current knowledge with regard to the causation, clinical signs and treatment. The book is aimed to provide those clinicians interested in children's diseases and basic scientists with a comprehensive resource covering the various aspects of bone health and disease in children Key Features * Deals exclusively with bone development and diseases of children and each chapter written by an * Fully referenced providing an appendix of usually difficult to find information on the investigation of pediatric bone disease and reference values * Covers both the physiology of bone and mineral homeostasis in children and diseases in one book * Includes a CD-ROM of images.